Determinants Affecting the Adoption of E-commerce and Its Impact on Organisational Performance of SMEs in Sri Lanka - Fonseka, Kapila; Jaharadak, Adam Amril; Raman, Murali; Tham, Jacquline (Journal of Telecommunications and the Digital Economy, 2021)
The Internet has become the best innovative driver in the fourth industrial revolution, transforming businesses into a technological era with speed and cost-effectiveness. E-commerce is one of the modern business strategies used by many companies to expand their market without limiting its geographical boundaries. This business strategy was initially used by companies in developed countries and eventually adopted by developing countries. Sri Lanka is a developing country and e-commerce penetration is far below other countries in the region. Perceived benefits, transformational leadership, and competitive pressure are the influencing factors of e-commerce adoption. The Technology-Organization-Environment and Diffusion of Innovations theories were used as the base of this research, and 350 samples were collected from the senior managers of SMEs. All factors significantly influenced e-commerce adoption and that positively affected the organisational performance of SMEs in Sri Lanka.